Pemilihan Saham Syariah yang Efisien untuk Pembentukan Portofolio Optimal - Nur Rachmat Arifin; Raditya Sukmana (ITB AAS INDONESIA Surakarta, 2019)
Abstract: Analysis of optimal portfolio allows investors to analyze appropriate to minimize the risks accepted by the objective of maximizing profit with the same risk among existing stocks. Data Envelopment Analysis (DEA) is used to determine the stocks with the efficient performance based on ratio analysis. Having selected some stocks efficient formation of optimal portfolio is then performed with a single index models and determined how much the proportion of funds invested in each stock. The sample data used are stocks in ISSI 2012-2017. Based on the analysis of efficiency as a candidate portfolio models used DEA - CCR and DEA - BCC generate 16 efficient stocks that forming the candidate portfolio. After the analysis of all 18 stocks that efficiently obtained 6 stocks forming the optimal portfolio Keywords: Optimal Portfolio,Data Envelopment Analysis (DEA), Efficiency Stocks, Relative Efficiency Score , Single Index Model.